Perancangan E-Learning dengan Menggunakan Learning Management System (LMS) - Setiyo W, L. Anang (Widya Warta, 2013)
E-learning is a method of learning  currently being developed at several universities in Indonesia. By making use of electronic and computer as its  medium, e-learning provides an innovation that greatly contributes to changes in teaching and learning  processes in which learners  no longer listen merely to the description of material provided by lecturers, but e- learning may also become a simulation, multimedia, or direct and indirect interaction with the lecturers. The supporting infrastructure of e-learning at Catholic University of Widya Mandala Madiun can be used to build a web portal for e-learning. The students who have their own laptops  connected to the campus hotspot webs are about 200 in number. It is a good step to start building e-learning at the campus. In this planning process, the software used is open source. Linux ubuntu is used for operating system server, while xampp is used to build web server and Dokeos is used for its e-learning application.